THE IMAGE OF RUSSIANS IN TRAVEL GUIDES OF THE LATE 18TH – THE EARLY 19TH CENTURY (Південний архів (історичні науки), 2023)
The purpose of the research is to study the image of Russians who moved to the territory of Southern Ukraine on the basis of the travelogues of the late 18th – the first half of the 19th century. The methodological foundation of the research comprises such methods as analysis, synthesis, and also the frontier method and the method of local history. The main research results. It was the end of the 18th – the first half of the 19th century, when substantial geopolitical changes occurred in the south-eastern region of Europe: the southern territories of Ukraine were incorporated by the Russian Empire. This event caused migration of the Russian-speaking population to the south-eastern region and its colonization aimed at incorporation of the South of Ukraine in the general Russian life space. Due to the targeted support of the government, Russians occupied substantial territories of the South of Ukraine. Such territorial-political transformations resonated in many visitors of the Southern Ukrainian region. These epochal changes made many Russians and foreigners describe the course of transformations in their travel notes and appreciate their significance. In the late 18th – the first half of the 19th century the region was visited by representatives of nobility and merchants, scientists and ordinary travelers who left a large number of travel notes which became a valuable resource for depicting the image of Russians in the south-eastern region of the investigated period. In their travel notes, the visitors shared their personal impressions of their experiences, and similar materials cannot be found in other types of historical sources which were compiled under control of the Russian legislative bodies or were censored. One of the themes of the travelogues was depiction of the life of Russians in the new territories. The central subject of the travel notes was everyday life and character of migrants from Russian gubernias, living in the South of Ukraine. Conclusions. The research findings allowed identifying differences in the descriptions and evaluations of the character and the life style of Russians by foreign and Russian travelers in the investigated period. On the whole, the image of Russians was depicted against the background of opposing the fundamental categories – elite/common people, freedom/slavery, nation/ common people.
Keywords: travel guides, travel notes, tourism, travelers, South of Ukraine, travelogues